Methemoglobinemia due to use of poppers: a case report - Emmanuelle Sonck; Eric Bourmanne; Julien Bruteyn; Waheed Dolip (Journal of Medical Case Reports, 2022)
Abstract Background Methemoglobinemia is an excess of oxidized hemoglobin in the blood, affecting oxygen transportation. It is characterized by central cyanosis that does not respond to oxygen therapy. Prognosis is excellent when treated adequately and rapidly. We present a case report of a 38-year-old Caucasian man suffering from methemoglobinemia due to the use of poppers. Case presentation A 38-year-old Caucasian man known as a smoker and addicted to cocaine was admitted to the emergency department with dyspnea, agitation, and central cyanosis that started approximately 3 hours before admission. The persistent hypoxia despite high-flow oxygen therapy and a history of poppers use helped to reveal a condition known as methemoglobinemia. Conclusions Our case highlighted a typical clinical presentation of methemoglobinemia. This possible life-threatening condition can occur after ingestion or inhalation of poppers, commonly sold in sex shops for recreational purposes. This can be easily confirmed by the methemoglobin level of the blood gases, provided the emergency physician considers this diagnosis. Rapid treatment with intravenous methylene blue is effective and leads to a favorable prognosis.